Changing roles and statuses of women in Thailand : documentary assessment - Yoddumnern, Bencha (Nakhonpathom, Thailand : Institute of Population and Social Research, Mahidol University, 1992)
Contributed articles
Bibliography : p. 105-116 and index
Keywords: Women -- Thailand -- Social conditions